2001
DOI: 10.1111/j.1744-6570.2001.tb00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Understanding of Employment Discrimination Claiming: An Integration of Organizational Justice and Social Information Processing Theories

Abstract: This research examines predictors of actual discrimination claiming among terminated workers by investigating a number of variables suggested by organizational justice and social information processing theories. This study investigated initial decisions to claim in a sample of 439 terminated workers who were surveyed at several unemployment offices. Logistic regression was used to examine how the decision to claim for discrimination was affected by procedural and distributive justice, social guidance, minority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(119 citation statements)
references
References 56 publications
6
112
0
Order By: Relevance
“…This idea of whistleblowing in the sense of following duty is connected to what Near and Miceli (1996: 511) call role-prescribed forms of reporting, referring to instances where individuals consider it their role responsibility to report wrongdoing. Hierarchy also implies that there is a sense of fairness about the system and internal procedures, which is in accordance with the findings in empirical research that individuals are more inclined to report misconduct when they perceive the organisation to be more just (Near et al, 1996: 511), or in other words when they think the organisation has a higher intensity of procedural and retributive justice (Victor et al, 1993;Goldman, 2001). The hierarchical decision not to blow the whistle on colleagues' misbehaviour is inspired by the idea that it is not your role or your responsibility to do so.…”
Section: Four Types Of (Not) Reporting Colleagues' Misconduct In Ggctsupporting
confidence: 69%
“…This idea of whistleblowing in the sense of following duty is connected to what Near and Miceli (1996: 511) call role-prescribed forms of reporting, referring to instances where individuals consider it their role responsibility to report wrongdoing. Hierarchy also implies that there is a sense of fairness about the system and internal procedures, which is in accordance with the findings in empirical research that individuals are more inclined to report misconduct when they perceive the organisation to be more just (Near et al, 1996: 511), or in other words when they think the organisation has a higher intensity of procedural and retributive justice (Victor et al, 1993;Goldman, 2001). The hierarchical decision not to blow the whistle on colleagues' misbehaviour is inspired by the idea that it is not your role or your responsibility to do so.…”
Section: Four Types Of (Not) Reporting Colleagues' Misconduct In Ggctsupporting
confidence: 69%
“…Moreover, presenting information may reduce the proportion of applicants perceiving the process as unfair, something that may be important given the relationship between fairness and outcomes such as litigation (Goldman, 2001). Information about a test or process and explanations for delays in scoring can be easily and inexpensively presented to applicants.…”
Section: Discussionmentioning
confidence: 99%
“…In part, this is why employee referrals often are seen as a good source of applicants (see Zottoli & Wanous, 2000 for a review of the literature on recruiting sources). Also, Goldman (2001) demonstrated that the strongest predictor of discrimination-claiming behavior was social guidance, or the perceptions of family and friends that one had been treated unfairly. Ryan and Ployhart (2000) concluded that social information has been somewhat neglected in the applicant perceptions literature (with the exception of Bazerman, Schroth, Shah, Diekmann & Tenbrunsel, 1994, which showed that friends can influence one's perceptions of job offers).…”
Section: Directmentioning
confidence: 99%